Effect of irrigation methods and fertilizer levels on yield of potato (Solanum tuberosum) - PAWAR, D D; BHOI, P G; SHINDE, S H (The Indian Journal of Agricultural Sciences, 2014)
The experiment was conducted during 1998-99 and 1999-2000 to assess the comparative performance of different irrigation methods in relation to productivity and economic retuins and to find out optimum fertilizer dose for winter season potato (Solanum tuberosum L.). Total 18 treatments comprising 3 irrigation methods, viz drip, sprinkler and surface, and 6 fertilizer treatments, viz 80, 40 and 40 kg; 120,60 and 60 kg; 160,80 and 80 kg; 80, 40 and 80 kg; 120,60 and 120 kg; and 160,80 and 160 kg N, P and K/ha, with 6 replications were undertaken in split-plot design. The sprinkler and drip irrigation systems resulted in significantly higher potato tuber yield to the extent of 43.5 and 21.2 %, respectively, compared with conventional surface method. The sprinkler method of irrigation gave maximum net returns (Rs 42 850/ha) and benefit: cost ratio (2.93). Drip irrigation system saved 39% water compared with other systems, but high initial investment for drip resulted in the lowest benefit: cost ratio which made it less economical for close growing crop like potato. The fertilizer dose of 120,60 and 120 kg N, P and K/ha resulted in significantly higher potato tuber yield than all lower and higher fertilizer levels and found optimum for potato.